Hubungan minat baca dengan kemampuan menyelesaikan soal cerita matematika Kelas V SDN Se-Kecamatan Terbanggi Besar - Alifia Putri Maharani; Jenny Indrastoeti Siti Poerwanti (Didaktika Dwija Indria, 2025)
The objective of this study is to ascertain the correlation between a person’s reading interest and their capacity to tackle mathematical story problems.. This research is descriptive quantitative research with a correlational approach. The research population was all fifth grade students of SDN in Terbanggi Besar District. Cluster random sampling was used to select the 125 participant for this study. The data collection technique uses a reading interest questionnaire. According to the findings of this study, a strong and favorable correlation exists between an interest in rrading and the capacity to answer mathematical word problems. The results are shown from the results of simple correlation calculations with a Pearson Correlation value of 0.858 with the information that there is a very strong relationship between variables.